Adolescent institutionalization in semi-liberty: the scenario of social and health vulnerabilities in an Amazon region - Rodrigues de Souza, Paolla Sabrina; Santos de Sousa, Gutembergue; Machado de Aguiar Lima, Maria Mônica; Macambira Santana Lima, Yara; Ferreira Coelho Galvão, Edna; Silva Ferreira, Maria Goreth (O Mundo da Saúde, 2022)
Violence and the practice of breaking the law are linked to the process of one’s identity, facts that end up constituting the identity of the adolescent who commits infractions. In this sense, this article aims to describe the socio-epidemiological profile of the population of detained adolescents in semi-liberty in the municipality of Santarém, state of Pará. This was an epidemiological, descriptive, and retrospective cross-sectional study with a quantitative approach, based on the analysis of medical records of adolescents treated at the Semi-Liberty Center of the Foundation for Socio-Educational Assistance of Pará, between January 2013 and June 2017. Among the results found were: the age group with the highest incidence was between 16 and 17 years (n= 42; 60%), mostly mixed race (n= 54; 77%), low levels of education with prevalence of incomplete elementary education (n= 54; 77%), members of low-income families, drug users (n= 65; 93%), and robbery and homicide were the main crimes committed. In addition, mental illness (n= 10; 14%) and a history of Sexually Transmitted Infections - STIs (n= 9; 13%) were detected among the young people surveyed. Thus, it is observed that, according to the socio-epidemiological profile identified and given the vulnerability of this population, an intervention process is necessary based upon the actions of Primary Health Care, where health education acts as an instrument in the promotion of quality care for this population, and with their family they act on the factors that interfere in the process of this juvenile, in trouble with the law, becoming ill.